2008
DOI: 10.1186/1756-6614-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and cardiovascular risk in patients with a history of differentiated thyroid carcinoma: A case-controlled cohort study

Abstract: Hyperthyroidism seems to increase metabolic and cardiovascular risk, while the effects of subclinical hyperthyroidism are controversial. We evaluated metabolic and cardiovascular parameters in differentiated thyroid carcinoma (DTC) patients with suppressed thyrotropin (TSH) due to levothyroxine (L-T4) therapy. We studied DTC patients and, as a control group, patients with a history of surgery for non-malignant thyroid pathology. Significantly higher insulin and lower HDLcholesterol levels were recorded in DTC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
18
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 63 publications
6
18
2
Order By: Relevance
“…Contrary to what would be expected in the state of pharmacologically induced hyperthyroxinaemia, obesity is frequent in DTC patients [17], and our women were also overweight. It can therefore be hypothesised that the absence of significant deterioration in bone metabolism may be the result of a protective effect against bone mass loss and that this effect is due to the very state of being overweight or to the slowing down of the metabolism [18].…”
Section: Considerations On Frcontrasting
confidence: 99%
“…Contrary to what would be expected in the state of pharmacologically induced hyperthyroxinaemia, obesity is frequent in DTC patients [17], and our women were also overweight. It can therefore be hypothesised that the absence of significant deterioration in bone metabolism may be the result of a protective effect against bone mass loss and that this effect is due to the very state of being overweight or to the slowing down of the metabolism [18].…”
Section: Considerations On Frcontrasting
confidence: 99%
“…The range of normal body fat is 2%-5% in men and 10%-13% in women, while the obesity range of body fat percentage is above of 25% in men and 32% in women[53,54]. Experimentally, it was observed that BMI = 30 kg/m 2 implies approximately 30% of BF% at 20 years of age but increase to 40% at 60 year in men, while in older women these values were to 40% and 50%, respectively.…”
Section: Obesity Assessmentmentioning
confidence: 99%
“…High fibrinogen level may be associated with an elevation of von Willebrand factor in DTC. This may alter platelet plug formation which can lead to endothelial dysfunction and enhanced cardiovascular risk (Giusti et al, 2008). The mean value of total cholesterol (165.28±25.61) and LDL (100.84±27.11) were found to be decreased in DTC patients when compared to the mean value of total cholesterol (183.64±26.34) and LDL (116.97±27.75) in controls; p-value (0.001*).…”
Section: Discussionmentioning
confidence: 81%